Osobowościowe predykatory zachowań wyborczych. Rozważania w kontekście modelu „Wielkiej Piątki” - Turska-Kawa, Agnieszka (Political Preferences, 2011)
The five factor model of personality, so called "Big Five" of Paul T. Costa, and Robert R. McCrae is a valuable tool for researchers of individual differences, as it assumes the existence of supracultural and suprademographic and structurally most general personality dimensions, allowing for full and comprehensive characterization. The subject of the article are two factors of the "Big Five" model - openness to experien- ce and agreeableness. Given their characteristics and the analysis described in the literature on the research subject, the author assumed that the political preferences of individuals with varying levels of the analyzed factors will vary also. There will also be a difference in their political behavior in terms of political activity - passivity. Diagnosis of openness to experience and agreeableness was conducted based on the NEO-FFI Personality Inventory of Paul T. Costa and Robert R. McCrae in the Polish adaptation of Bogdan Zawadzki, Jan Strelau, Piotr Szcze- panik, and Magdalena Sliwinska.